An fMRI Study of the Neural Systems Involved in Visually Cued Tactile Top-Down Spatial and Temporal Attention - Wu, Qiong; Li, Chunlin; Li, Yujie; Sun, Hongzan; Guo, Qiyong; Wu, Jinglong (Neuroscience and Biomedical Engineering (Discontinued), 2014)
Top-down attention to spatial and temporal cues has been thoroughly studied in the visual and auditory domains. However, the neural systems that are important for tactile top-down temporal attention (i.e., attention based on time interval cues) remain undefined. Thus, the differences in brain activity between directed attention to tactile spatial location and time intervals are unclear. We measured brain activity during a task in sixteen healthy volunteers with functional magnetic resonance imaging (fMRI). The task manipulated cued attention to spatial locations (S) and temporal intervals (T) in a factorial design. Symbolic central cues oriented the subjects toward S only (left or right), toward T only (600 msec or 1800 msec), or toward both S and T simultaneously (no information was provided regarding S or T). The behavioral data indicated that the benefits and costs of performance during temporal attention were similar to those established for tactile spatial attention. The brain-imaging data revealed a partial overlap between neural systems involved in the performance of spatial versus temporal orientation of tactile attention tasks.
Keywords: orienting of attention